Analysis of Transaction Capability in Gate In-2 Automation Export at PT Terminal Petikemas Surabaya uses Control Chart - Chairunissa Kusnoaji; Iis Dewi Ratih (Institut Teknologi Sepuluh Nopember, 2021)
PT Terminal Petikemas Surabaya is an international standard container terminal that always makes innovations to improve the quality of container export and import services. OCR is a container data identification tool that has begun to be used at the gate in the automation of exports of PT Terminal Petikemas Surabaya. The existence of OCR at the gate in export automation creates a new time motion for transactions that need to be known about the processing capabilities. Using the control chart and Ishikawa diagram, it is found that the time motion transactions that occur at the gate in automation exports of PT Terminal Petikemas Surabaya are statistically out of control and incapable of being caused by many factors, both internal and external.